Intentional Online Discussions in Teacher Education. Issue 2 (3rd April 2018) - Piro, Jody S.; Anderson, Gina
ABSTRACT: The goal of a creating civil discourse in teacher education deeply intersects with the ways that students interact in online discussions. However, as discussion shifts to online formats, digital misinformation is becoming widespread and threatens critical and civil communication as cognitive biases emerge in dialogue. The purpose of this case study research was to explore the participants' perceptions of growth and pitfalls while using the six essential elements of an online discussion typology developed as a pedagogical intervention to increase critical thinking and civility in discourse. The findings suggested that participants' responses in online discussions implied some cognitive biases and those participants engaged most often in discussions that were safe, comfortable, and familiar. Nevertheless, in their metacognitive reflections on the typology, participants demonstrated awareness of how these tendencies toward cognitive comfort shortchanged discussions and potential opportunities to develop new perspectives.